Suture anchor fixation may be an alternative to tension band wiring in olecranon fractures: Finite element analysis - Kuru, Tolgahan (Jt Dis Relat Surg, 2020)
OBJECTIVES: This study aims to analyze and compare total deformations with tension band wiring (TBW), intramedullary screw (IS) and novel suture anchor (SA) fixation methods, and to investigate practicality of SA fixation in olecranon fractures using finite element analysis (FEA). MATERIALS AND METHODS: This finite element analysis study was conducted between May 2019 and October 2019. TBW, IS and SA fixation methods were compared in order to analyze fracture behavior in the ulna and humerus using FEA, which is among the mathematical methods of stress analysis. Boundary conditions were applied to the created model and total deformation amounts were compared among the methods in terms of displacement. RESULTS: The lowest amount of displacement was obtained with TBW method (1.2095 mm), while IS method (2.7703 mm) showed the highest amount of total displacement. Total displacement was lower with SA system (2.0397 mm) compared to IS fixation. In addition, no problem was observed with SA system in terms of failure occurrence. CONCLUSION: According to the results of FEA, although the lowest amount of displacement was obtained with TBW, it is concluded that anchor fixation method may be an alternative with practicality and mechanical properties. However, further studies are needed to obtain more precise data.